Evaluadores de este número - Graciela Tonon (Journal de Ciencias Sociales, 2014)
Dra. Graciela Cruz Jiménez, Universidad Autónoma del estado de MéxicoDra. Beatriz Arita Watanabe, Universidad de Sinaloa, México.Mag. Norma del Rio, Universidad Autónoma Metropolitana-Xochimilco, México.Dr. Alejandro Acosta Ayerbe, CINDE, Colombia.Dr. Norberto Méndez, Universidad de Buenos Aires.Dr. José Burucua Universidad Nacional de San Martín.Dr. Mariano Bartolomé, Universidad de Belgrano.Mag. Marcelo Montes, Universidad Nacional de Villa María.